2016
DOI: 10.1371/journal.pone.0165586
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Nerve Growth Factor Signaling Reduces the Neural Invasion Potential of Pancreatic Cancer Cells

Abstract: Perineural invasion (PNI) is thought to be one of the factors responsible for the high rate of tumor recurrence after surgery and the pain generation associated with pancreatic cancer. Signaling via the nerve growth factor (NGF) pathway between pancreatic cancer cells and the surrounding nerves has been implicated in PNI, and increased levels of these proteins have been correlated to poor prognosis. In this study, we examine the molecular mechanism of the NGF signaling pathway in PNI in pancreatic cancer. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 34 publications
(77 reference statements)
2
55
0
Order By: Relevance
“…Tumor cells have been shown to attract nerves, presumably by secreting neurotrophins (NT) such as NGF, BDNF, NT3, and NT4. NTs are a family of growth factors that stimulate nerve growth and mediate axonal guidance, synaptic plasticity and protection of nerves from injury, but can also act as autocrine growth factors and potentiate tumor cell invasion (Bapat et al, 2016). In this respect, it is important to note that intra- and extra-pancreatic perineural invasion by cancer cells is present in 71%–100% of PDAC resection specimens, and associated with worse patient survival (Liebl et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells have been shown to attract nerves, presumably by secreting neurotrophins (NT) such as NGF, BDNF, NT3, and NT4. NTs are a family of growth factors that stimulate nerve growth and mediate axonal guidance, synaptic plasticity and protection of nerves from injury, but can also act as autocrine growth factors and potentiate tumor cell invasion (Bapat et al, 2016). In this respect, it is important to note that intra- and extra-pancreatic perineural invasion by cancer cells is present in 71%–100% of PDAC resection specimens, and associated with worse patient survival (Liebl et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nerve‐tumour interaction has been a widely accepted theory of the pathogenesis of PNI. It has been reported that autocrine or paracrine phenomena involving soluble factors and their receptors such as neurotrophic factors, chemokines and neuropeptides play important roles in the crosstalk between nerves and tumours. In addition to neurone and cancer cells, other cell types have also been demonstrated to be involved, including supporting cells, Schwann cells and endoneurial macrophages .…”
Section: Introductionmentioning
confidence: 99%
“…such as neurotrophic factors, [15][16][17][18] chemokines 19,20 and neuropeptides 21,22 play important roles in the crosstalk between nerves and tumours. In addition to neurone and cancer cells, other cell types have also been demonstrated to be involved, including supporting cells, Schwann cells and endoneurial macrophages.…”
mentioning
confidence: 99%
“…Increased expression of NGFR or both NGFR and Trks was also shown in ovarian cancer, neuroblastoma, renal cell carcinoma and Schwannomas, whereas NGFR expression has been shown to be decreased in both gastric cancer and hepatocellular carcinomas . In addition, the possibility to target neurotrophin receptors was shown in several of the cited here over as well as for melanomas and pancreatic cancer cells . The potential role of KIDINS220 was not evaluated in any of these studies on neurotrophin‐receptors and cancer, but due to its central position in neurotrophin signalling, we imagine that it's involved as well.…”
Section: Kidins220 and Cancermentioning
confidence: 95%
“…78 In addition, the possibility to target neurotrophin receptors was shown in several of the cited here over as well as for melanomas 79 and pancreatic cancer cells. 80 The potential role of KIDINS220 was not evaluated in any of these studies on neurotrophin-receptors and cancer, but due to its central position in neurotrophin signalling, we imagine that it's involved as…”
Section: Indirect Roles Of Kidins220 In Cancermentioning
confidence: 99%